Balkanske pokrajine in ženska želja v treh novelah pisateljic s konca 19. in začetka 20. stoletja - Mihurko, Katja (Slavia Centralis, 2024)
This article analyses the representation of female sexual desire in the works of three authors set in the Balkans. It is based on the hypothesis that the concept of the Balkans was still in its formation in the 19th century and therefore offered opportunities for the projection of various ideas. As such, it also served as a backdrop for three stories in which the authors (Mara Čop Lenger- Marlet, Milena Mrazović-Preindlsberger and Zofka Kveder) featured three female characters who transcended the boundaries of normative femininity.
Keywords: Mara Čop Lenger-Marlet, Marie von Berks, Milena Mrazović- Preindlsberger, Zofka Kveder, female sexual desire, intimacy, the Balkans, gender, in-between identity